Analysis of Factors Influencing Purchase Intention of Barenbliss Powder Mediated by Consumer Attitudes in Payakumbuh City - Suci Fresti Putri; Winny Alna Marlina; Faisal Ali Ahmad (Green Publisher Indonesia, 2025)
Barenbliss is a cosmetics brand from South Korea that entered Indonesia in 2021. The study aims to see the effect of the effectiveness of social media communication on purchase intentions at Barenbbliss Powder in Payakumbuh City with consumer attitudes as mediation. This study used a quantitative method, the respondents in the study amounted to 194 samples, then the data was processed and analyzed using the SEM-PLS analysis method with the help of SmartPLS software version 4.0. The results of the study showed that the variables of source credibility and information quality had no effect on the effectiveness of social media communication at Barenbliss Powder in Payakumbuh City.The brand credibility variables, accuracy of information were positively and significantly related to the effectiveness of social media communication at Barenbliss Powder in Payakumbuh City. The variables of social media communication effectiveness have a positive and significant relationship with consumer attitudes on Barenbliss Powder in Payakumbuh City. The variables of consumer attitudes are positive and significant towards purchase intentions in Barenbliss Powder in Payakumbuh City. The variable of full consumer attitude mediated the relationship between the effectiveness of social media communication and purchase intention for Barenbliss Powder in Payakumbuh City.